Optimization Of The Quality Of Life Of The Elderly Through Counseling And Elderly Exercise Programs In Terusan Baru Village - Aan Junaidi; Ade Irma Suryani; Chesti Idawati; Emilia Contesa; Arie Wujaya (Universitas Dehasen Bengkulu, 2026)
. Elderly people are an age group that is vulnerable to various health problems, including declines in physical, cognitive, and social functions. Health education programs and elderly exercise (senam lansia) are important strategies to improve their quality of life. This study aims to analyze the role of health education and elderly exercise in enhancing physical fitness, health awareness, and independence among the elderly. The method used is community service through health education activities, exercise demonstrations, and evaluations of participants’ fitness and health knowledge. The expected outcomes are increased participation of the elderly in physical activities, understanding of healthy lifestyle habits, and the ability to maintain their health independently. Thus, this program can serve as an effective intervention model to improve the quality of life of the elderly in local communities.